336 - Centrally administered prostaglandin E2 suppresses the rat micturition reflex via brain EP1 and EP2 receptors - Shimizu, T; Shimizu, N; Tsubouchi, S; Togo, M; Higashi, Y; Saito, M (Continence (Amsterdam), 2025)
Prostaglandin E2 (PGE2) is reported to facilitate the micturition reflex at levels of the lower urinary tract (LUT) and the spinal cord [1]. However, roles of brain PGE2 in regulation of the reflex are unclear. In previous reports, intracerebroventricularly (icv) administered PGE2 elevated plasma noradrenaline [2], which can affect the micturition reflex. In this study, therefore, we investigated effects of icv administered PGE2 on the rat micturition reflex. In urethane-anesthetized (0.8 g/kg, ip) male Wistar rats (300-450 g), a catheter was inserted into the bladder to perform cystometry. Two hours after the surgery, cystometry (saline instillation at 12 ml/h) was started to evaluate intercontraction interval (ICI), threshold pressure for inducing micturition (TP) and maximal voiding pressure (MVP). One hour after the start, PGE2 (0.1, 0.3 or 1 nmol/rat) or vehicle was icv administered. Evaluations of these parameters were continued 2 h after the administration. When using each antagonist for E-prostanoid receptor subtypes (EP1-EP4), SC51322 (EP1 antagonist), PF04418948 (EP2 antagonist), L-798106 (EP3 antagonist) or L-161982 (EP4 antagonist) was icv pretreated at 100 nmol/rat 30 min before PGE2 administration (1 nmol/rat, icv). In some rats, 6-hydroxydopamine (6-OHDA), which induces chemical sympathectomy, was administered (100 mg/kg, ip) once a day for 3 days. At one day after the third administration, PGE2 was administered (1 nmol/rat, icv) and urodynamic parameters were evaluated in addition to measuring mean blood pressure (MBP) through an arterial catheter. PGE2 dose-dependently increased ICI and TP (Fig. 1) without changing MVP (data not shown). In 6-OHDA-pretreated rats, baseline values of MBP were significantly decreased compared to those in vehicle-pretreated control rats (96.3±4.2 vs 108.0±1.9 mmHg, P<0.05). PGE2 at 1 nmol significantly increased MBP and the increment was abolished by 6-OHDA (Fig. 2A). On the other hand, 6-OHDA showed no significant effect on the PGE2-induced increments in ICI or TP (Fig. 2B-2C). Icv pretreated SC51322 and PF04418948, but not L-798106 or L-161982, significantly attenuated the PGE2-induced increments in ICI and TP (Fig. 3). Icv administered PGE2 increased ICI and TP, and TP can be increased by urethral contraction. Since icv administered PGE2 was reported to elevate plasma noradrenaline [2], the PGE2-induced ICI increments might be mediated at least by increased urethral resistance induced by noradrenaline. In 6-OHDA-pretreated rats, chemical sympathectomy was induced evidenced by decreased basal MBP. Icv administered PGE2 increased MBP and the increment was abolished by 6-OHDA, which showed no effect on the PGE2-induced increments in ICI or TP. Therefore, it is assumed that centrally administered PGE2 suppressed the rat micturition reflex independently of the sympathetic nervous system (SNS) activation. Our results of experiments using EP receptor antagonists suggest that brain EP1 and EP2, but not EP3 or EP4, receptors are involved in the PGE2-induced suppression of the micturition reflex. Previously, it is reported that in rats, icv administered PGE2 increased bladder capacity (BC), while local administration of PGE2 into the periaqueductal gray (PAG) decreased BC through EP1 receptors [3]. In addition, PGE2 administered into the PAG decreased BC at 28 pmol, but not 280 pmol, in rats [3]. These data suggest that roles of brain PGE2 in regulation of the micturition reflex might be vary depending on action sites and local contents of brain PGE2. Further studies are needed to clarify brain specific regions that contribute to brain PGE2 and EP1/EP2 receptors-mediated suppression of the micturition reflex. Centrally administered PGE2 suppresses the rat micturition reflex via brain EP1 and EP2 receptors independently of the SNS activation. Therefore, brain PGE2 and EP1/EP2 receptors could be novel therapeutic targets for patients with LUT dysfunctions attributed to neurogenic bladder overactivity. [Display omitted] [Display omitted] Funding JSPS KAKENHI Grant (#23K06887), Grant from The Smoking Research Foundation in Japan and The Kochi Medical School Hospital President’s Discretionary Grant. Clinical Trial No Subjects Animal Species Rat Ethics Committee The Kochi University Institutional Animal Care and Use Committee